A critical review of the Hong Kong new competition regime: a comparative perspective of objectives, institutions, and scope - Chiang, CH (2017)
This thesis examines the effectiveness of the competition regime in Hong Kong (HK), which is one of the few remaining developed economies to yet implement a competition law. In its search for the optimal dynamics of the regime, the thesis offers a tripartite examination on its objectives, institutions and scope of application, and how these three distinct internal dimensions individually and jointly influence the effectiveness of the regime. Furthermore, a critical review is offered on two significant external factors, land hegemony and the political regime, both of which exert a strong force on the competition regime. This interdisciplinary research project encompasses legal, political, economic, and market-contextualized analysis. Given that HK has a new competition regime, and is an international financial, communication, and transportation centre, it is appropriate and apposite to evaluate it by international standards. The thesis begins with an examination of three internal dimensions. As a preliminary, it considers the extent to which HK benefits from a free economy with a sound competitive environment. It then moves on to investigate the first dimension, which is that of the objectives of the competition law in terms of its clarity, prioritization and consistency. Following this, the thesis investigates the second dimension, the institutions of the Competition Commission and the Competition Tribunal, by asking how the structure shapes the substance of enforcement. It explores the limitations and virtues of major institutional models and which model is the most appropriate for HK. In its third dimension, the thesis questions the adequacy of the scope of competition law, with a focus on the near blanket exclusion of public entities. Commentary is offered on how to achieve a level playing field between private and public sectors. Following the evaluation of the three internal dimensions, the thesis focuses on their correlations. The discussion reviews the challenges and puts forward a wide range of measures to manage them. Finally, the thesis explores the significance of two external powers, land hegemony and political regime, and suggests several long-term solutions which the author believes would lead to the steady optimization of the competition regime.